ตัวประกอบสมรรถนะของพยาบาลวิชาชีพหน่วยงานอุบัติเหตุและฉุกเฉินในโรงพยาบาลของรัฐ - อรทัย ปึงวงศานุรักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1997)
The purposes of this research were to study the factor competencies of emergency department nurses and the variables which described those major factors. The participants in this study were 1031 emergency department nurses. Governmental hospitals all over the country, who had been at least one year of experience. The instrument was a rating scale on frequencies of important competencies of emergency department nurses. The reliability of the instrument, calculated by the Cranach Alpha Coefficient was .9867. The data were analysed by Image Factoring method, Orthogonal rotated axis by Varimax method, Orthogonal rotated axis by Varimax method. The major findings were as follows: Nine significant factiors competencies of emergency nurses were determined: 1) Emergency Symptom Assessment, a major factor of emergency nurse’s competencies, which described by 29 items, items, accounted for 39.5 percent of total variances, 2) Leadership. Which described by 16 items, accounted for 4.4 percent of total variances, 3) Law, Ethics and Emergency Operation Management, which described by 20 items, accounted for 2.8 percent of total variances, 4) Emergency Nursing Practice, which described by 21 items, accounted for 206 percent of total variances, 5) Emergency Nursing in Critical III Patient, which described by 9 items, accounted for 1.9 percent of total variances, 6) Management in Emergency Department, which described by 6 items , accounted for 1.6 percent of total variances, 7) Planning in Emergency Nursing, which described by 7 items, accounted for 1.2 percent of total variances, 8) Academic in Emergency Nursing, which described by 7 items, accounted for 1.1 percent of total variances 9) Advanced Life Support, which described by 3 items, accounted for 0.9 percent of total variances. The total variance of these factors is 56.0 percent accumulative.